The politics and construction of identity and childhood: Chinese immigrant families in New Zealand. Issue 1 (March 2017) - Chan, Angel; Spoonley, Paul
Diverse immigrants have significantly transformed the ethnic make-up of New Zealand, and they have brought with them diverse identities to this country. Findings from a doctoral research project which involved exploring Chinese immigrant parents' identity choices for themselves and their children highlight the complex politics of identity. Within the field of education, children's acquisition of a positive identity is closely related to valued self-worth, and a sense of shared identity is further believed to promote beneficial relationships, sense of belonging and social cohesion. Identity theories, nonetheless, argue that contemporary individual identities are fluid and hybrid, and an over-emphasis on collective identity creates boundaries, exclusion and tension. This article applies some of these theoretical frames to critically examine the identity choices of Chinese immigrant parent participants and argues for the need to re-examine the notion of identity. The implications of these identity choices on their children's childhood and social and education practices are also analysed.